KUALITAS PELAYANAN DAN PEMBAYARAN NON TUNAI: DAMPAKNYA TERHADAP OMSET PENJUALAN PADA GEROBAK KREATIF DI KOTA DENPASAR - MARTINI, LUH KADEK BUDI; FARHAENI, MUTRIA; WIDIASTUTI, NI PUTU; UDAYANA, PUTU SUWECA NATA (Universitas Mahasaraswati K. Mataram, 2024)
This research is descriptive and analytical, utilizing a quantitative approach. The sample was selected using purposive sampling, with a total of 30 respondents. Data were collected using a Likert scale questionnaire and processed with SPSS software. The results of the study indicate that: (1) Service quality has a positive and significant effect on the sales turnover of creative cart traders in Denpasar City's MSMEs, as evidenced by a t-value of 9.159 and a significance level of 0.000 < 0.05, suggesting that improving service quality will increase the sales turnover of these traders. (2) The non-cash payment system does not have a significant effect on the sales turnover of creative cart traders in Denpasar City's MSMEs, as shown by a t-value of 1.385 and a significance level of 0.177 > 0.05, indicating no influence of non-cash payments on sales turnover. (3) Service quality and the non-cash payment system collectively have a significant simultaneous effect on the sales turnover of creative cart traders in Denpasar City's MSMEs, with an F-value of 42.037 and a significance level of 0.000. The determination test results show that the variables of service quality and the non-cash payment system affect sales turnover by 73.9%, while the remaining 26.1% is influenced by other variables outside of this study, such as price, product quality, and promotion.